2005
DOI: 10.1002/mrm.20476
|View full text |Cite
|
Sign up to set email alerts
|

Determination of mouse skeletal muscle architecture using three‐dimensional diffusion tensor imaging

Abstract: Muscle architecture is the main determinant of the mechanical behavior of skeletal muscles. This study explored the feasibility of diffusion tensor imaging (DTI) and fiber tracking to noninvasively determine the in vivo three-dimensional (3D) architecture of skeletal muscle in mouse hind leg. In six mice, the hindlimb was imaged with a diffusion-weighted (DW) 3D fast spin-echo (FSE) sequence followed by the acquisition of an exerciseinduced, T 2 -enhanced data set. The data showed the expected fiber organizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
142
4

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 145 publications
(155 citation statements)
references
References 37 publications
7
142
4
Order By: Relevance
“…The interpretation of brain fiber tracking results is complex and requires detailed information about anatomy and the architecture of brain diffusion pathways (5,9,14,15). The landscape of skeletal muscle is not as complicated and therefore application of fiber tractography can, in principle, provide detailed information about muscle fiber architecture (16,19). In our work we applied fiber tractography to reconstruct calf muscle fibers in healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…The interpretation of brain fiber tracking results is complex and requires detailed information about anatomy and the architecture of brain diffusion pathways (5,9,14,15). The landscape of skeletal muscle is not as complicated and therefore application of fiber tractography can, in principle, provide detailed information about muscle fiber architecture (16,19). In our work we applied fiber tractography to reconstruct calf muscle fibers in healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…DTI has been successfully applied to the analysis and depiction of neuronal fibers in the living human brain (Mori and van Zijl, 2002). Furthermore, qualitative agreement between main diffusion directions and the fiber orientation in myocardium (Garrido et al, 1994;Reese et al, 1995;Scollan et al, 1998;Schmid et al, 2005) and skeletal muscle (Van Donkelaar et al, 1999;Napadow et al, 2001;Damon et al, 2002;Mori and van Zijl, 2002;Heemskerk et al, 2005) was observed.…”
mentioning
confidence: 88%
“…DTI provides information on skeletal muscle architecture by tracking the random diffusion of water molecules as it interacts with the internal structures that restrict its movement. A major advantage of DTI is that the diffusion of molecules can probe tissue structure with a high degree of sensitivity not typically provided by usual imaging procedures, thereby making it a useful technique for studying biological tissue architecture (Heemskerk et al, 2005). Moreover, this technique allowed us to evaluate the average dimensions of individual myofibers contained within whole muscle in contrast to the invasive biopsy that only represents a small portion of muscle.…”
Section: Magnetic Resonance Diffusion Tensor Imaging (Mr Dti)mentioning
confidence: 99%
“…λ1 has been proposed to represent diffusive transport along the long axis of the myofiber while λ2 and λ3 constitute transport perpendicular to the long axis (i.e. cross-sections) (Heemskerk et al, 2005). Fractional anisotropy (FA) can also be calculated, which refers to the degree by which diffusion occurs restricted or unrestricted, and is inversely related to myofiber crosssectional area.…”
Section: Magnetic Resonance Diffusion Tensor Imaging (Mr Dti)mentioning
confidence: 99%